Effects of sodium benzoate on growth and physiological characteristics of wheat seedlings under compound heavy metal stress - Pan-pan LIANG; Chen ZHAO; Yuan LIN; Ji-jia GENG; Yuan CHEN; De-hua CHEN; Xiang ZHANG (Journal of Integrative Agriculture, 2020)
In this study, we investigated the effect of exogenous sodium benzoate on wheat seedlings (Yangmai 16) grown under heavy metal stress. The results showed that 2.4 mmol kg−1 of heavy metals significantly inhibited growth and delayed emergence of wheat seedlings. Under compound heavy metal stress, application of 2–4 g L−1 sodium benzoate significantly increased (P>0.01) chlorophyll content and chlorophyll fluorescence parameters Fv/Fm and Fv/Fo of wheat, compared to the control (water treatment). Further analysis showed that application of 2–4 g L−1 sodium benzoate alleviated osmotic stress by promoting the accumulation of osmolytes such as soluble proteins and free proline, increased the activity of superoxide dismutase (SOD) and reduced malondialdehyde content (MDA). In contrast, higher concentrations of sodium benzoate solution (>6 g L−1) inhibited the growth of wheat seedlings and even caused damage to seedlings. Correlation analysis showed that when the sodium benzoate concentration was in the range of 1.97–3.12 g L−1 (2016) and 1.58–3.27 g L−1 (2017), values of chlorophyll and its components, root activity, SOD activity, soluble protein, and free proline content were the highest. When the sodium benzoate concentration was raised to 2.59 g L−1 (2016) or 3.02 g L−1 (2017), MDA content was the lowest. Ultimately, exogenous sodium benzoate (2–4 g L−1) facilitates root development and improves the root activity of wheat seedlings grown under compound heavy metals stress, thereby effectively alleviating the damage of compound heavy metal stress in wheat seedlings.